Metode Demonstrasi Dalam Meningkatkan Keterampilan Siswa Pada Mata Pelajaran PAI Di SMP Islam Masagi Kabupaten Sukabumi - Herdi Herdi; Kun Nurachadijat (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
To be able to create a creative learning atmosphere in Islamic Religious Education subjects, teachers can use the demonstration method, because in Islamic Religious Education lessons the scope is generally different from Madrasah schools which have been classified as having aqidah Akhlaq, fiqh, Qur'an Hadith, SKI, and some others. While in SMP, the scope is in PAI subjects. As for the material that is applied or practiced, such as how to pray, ablution, tayammum, and so on. In this approach we use descriptive qualitative research, which aims to describe a situation. Descriptive approach also means explaining phenomena and situations. This data collection technique takes place by means of an interview process, namely the process of obtaining information for research purposes by means of debriefing while face to face between the questioner or interviewer and the answerer or responses using a tool called an interview guide. Based on observations and interviews conducted by researchers, the teacher demonstrated learning materials such as prayer practices, dead prayers, reading the Qur'an with tartil according to the tajwid makhorijul letters and so on. With the aim that the students are able to understand and cultivate skills in studying well, especially in prayer, because that is the foundation in Islamic teachings, and that is also the goal of the Education Law Number 20 of 2023. The results of the mini research conducted by researchers with the title : "Demonstration Methods in Improving Psychomotor or Student Skills in PAI Subjects at Masagi Islamic Middle School, Sukabumi Regency." Students are able to demonstrate their skills and concentrate more on learning. This means that Islamic Education Subject Teachers have been using demonstration methods for a long time with the aim of improving students' psychomotor or skills, so the title of the researcher is very coherent and relevant to the conditions at the school.